PENGARUH KOMUNITAS BELAJAR DAN MOTIVASI BERPRESTASI TERHADAP KOMPETENSI PEDAGOGIK GURU SEKOLAH DASAR NEGERI SE-KECAMATAN TEMANGGUNG KABUPATEN TEMANGGUNG - Fitriyana Nur Azizah; Yovitha Yuliejantiningsih; Maryanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT: The background of the problem in this study is 1) the pedagogical competence of teachers is still in the category of needing improvement, 2) the implementation of learning communities is not optimal, 3) the achievement motivation of teachers is still lacking. This study aims to determine: 1) the effect of learning community on pedagogical competence of public elementary school teachers in Temanggung District; 2) the effect of achievement motivation on pedagogical competence of public elementary school teachers in Temanggung District; 3) the effect of learning community and achievement motivation on pedagogical competence of public elementary school teachers in Temanggung District. This study uses a quantitative approach with descriptive research, simple linear regression, multiple linear regression, correlation, effective contribution, and relative contribution. The population of this study were all principals and teachers of public elementary schools in Temanggung District of Temanggung Regency totaling 186 and the research sample was 127. Based on the results of the study, it can be concluded that 1) the relationship between learning communities and teachers’ pedagogical competence is included in the strong category. The magnitude of the influence of the learning community on the teacher’s pedagogical competence variable is 47.8%. 2) the relationship between achievement motivation and teacher pedagogical competence is included in the strong category. The magnitude of the effect of achievement motivation on teacher pedagogical competence variables is 47.2%. 3) Learning community, and achievement motivation simultaneously have a positive and significant effect on teacher pedagogical competence variables by 55.9%. Suggestions from researchers on pedagogical competence are to improve the quality of curriculum development and the flow of learning objectives. In addition, tis recommended to improve collaboration in collective learning, teachers must be actively involved in collective learning activities in learning communities. And teachers must consistently develop a positive attitude towards the teaching profession and always be oriented towards improving the quality of learning. Keywords: Learning community, Achievement motivation, Teacher Pedagogical Competence.